2018
DOI: 10.3847/1538-4357/aab3e7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Gas Reservoirs in Cluster Galaxies at z = 1.46

Abstract: We present molecular gas reservoirs of eighteen galaxies associated with the XMMXCS J2215.9-1738 cluster at z = 1.46. From Band 7 and Band 3 data of the Atacama Large Millimeter/submillimeter Array (ALMA), we detect dust continuum emission at 870 µm and CO J = 2-1 emission line from 8 and 17 member galaxies respectively within a cluster-centric radius of R 200 . The molecular gas masses derived from the CO and/or dust continuum luminosities show that the fraction of molecular gas mass and the depletion time sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(126 citation statements)
references
References 115 publications
(183 reference statements)
12
113
1
Order By: Relevance
“…In line with these results, Noble et al (2017) found depletion timescales systematically higher than the scaling relation for nine CO(3 − 2)-detected galaxies in a cluster at z ∼ 1.6, although most are within a one standard deviation of the relation (plus several non-detection whose upper limits are in agreement with the field). Similarly, Hayashi et al (2018) presented CO(3 − 2) observations in several cluster galaxies at z ∼ 1.5 finding again systematically longer depletion timescales, although ∼ 50% of their sample might be in agreement the expected relation for the field (when non-detections are taken into account).…”
Section: The Star Formation Efficiencysupporting
confidence: 65%
See 2 more Smart Citations
“…In line with these results, Noble et al (2017) found depletion timescales systematically higher than the scaling relation for nine CO(3 − 2)-detected galaxies in a cluster at z ∼ 1.6, although most are within a one standard deviation of the relation (plus several non-detection whose upper limits are in agreement with the field). Similarly, Hayashi et al (2018) presented CO(3 − 2) observations in several cluster galaxies at z ∼ 1.5 finding again systematically longer depletion timescales, although ∼ 50% of their sample might be in agreement the expected relation for the field (when non-detections are taken into account).…”
Section: The Star Formation Efficiencysupporting
confidence: 65%
“…The effects of the environment are more evident when looking at the fraction of quenched galaxies. The larger number of massive gas-poor galaxies (ALMA non-detections) in the proto-clusters in comparison to the field (Figures 4 and 7) suggests that these protocluster galaxies are undergoing an accelerated evolution (see also Hayashi et al 2018;Shimakawa et al 2018;Wang et al 2018). These massive gas-poor systems have low gas mass fractions of f gas 6 − 10 % (Figure 4) and red colors ( Figures 5 and 6) which are in agreement with those found for post-starburst and quiescent galaxies at lower redshifts (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our SFR thus converts into M mol =(1.5±0.6)×10 10 M , hence f mol ∼ 9 ± 4%. We compare it to CO or dust-continuum-based gas fractions and upper limits (converted to Salpeter) for quiescent and post-starburst galaxies: Davis et al (2014) and Saintonge et al (2011) for local massive PEGs; Sargent et al (2015), Bezanson et al (2019), Spilker et al (2018), Zavala et al (2019), Rudnick et al (2017), Suess et al (2017), Spilker et al (2018), Hayashi et al (2018), Gobat et al (2018) for intermediate-z quiescent galaxies; Schreiber et al (2018) and Valentino et al (2020) for z∼3-4 galaxies. Despite the uncertainties, our data at z∼3 seems to disfavor the steep (1+z) 4−5 trend inferred from z = 0 to 1.5-2, suggesting a flattening in the M mol /M evolution (or equivalently, of the sSFR).…”
Section: Discussionmentioning
confidence: 99%
“…Spilker et al (2018a) presented CO(2-1) observations of 8 massive and passive galaxies at z ∼ 0.7, in which we found very low gas fractions but also relatively short gas depletion times 1 Gyr. This picture largely continues to z ∼ 1.5 (Sargent et al 2015;Rudnick et al 2017;Hayashi et al 2018;Bezanson et al 2019), where a total sample of four quiescent galaxies all exhibit strikingly low gas fractions (t dep is more difficult to constrain as reliable SFRs become more challenging to measure). In summary, these observations of older quiescent galaxies all point to very efficient molecular gas depletion, in agreement with our current understanding of the future evolution of COSMOS 27289 following its imminent depletion of molecular gas.…”
Section: Comparison To Probable Progenitor and Descendant Populationsmentioning
confidence: 99%